Development of Multimedia Whiteboard Annimation to Improve the Understanding of Writing Scientific Papers of Non-Educational Students - Sri Sumiyati; Aini Indriasih; Mohamad Hariyono; Edi Prayitno; Sumaji Sumaji (STAI Hubbulwathan Duri, 2022)
This study aims to develop multimedia with whiteboard animation techniques to improve students' ability to develop scientific papers. The research method used is research and development (RD). The research and development steps are based on the four-D model, namely the defining stage (define), the design stage (design), the development stage (develop) and the dissemination stage (disseminate). The subjects in this study were Pokjar Cempaka Pati students consisting of 20 students. Data collection in the field was carried out using questionnaires given to non-basic students at the Faculty of Economics who took Scientific Paper courses. The data is analyzed descriptively, that is, it gives meaning to each data collected, and is presented in the form of percentages and graphs. The results showed that (1) based on the assessment of whiteboard animation media validators, it was a range of 82.00% - 96.00% of valid categories, (2) Whiteboard animation media is very effective in increasing understanding in student scientific work courses.